Research on iron deficiency anemia and risk factors in preschool children (Revista Brasileira Multidisciplinar, 2025)
Iron deficiency is identified as the main causal determinant of most cases of anemia, and is currently the most prevalent nutritional deficiency in the world, affecting developed and developing countries. Among the populations at risk for iron deficiency anemia, preschool children constitute a vulnerable group, raising concern due to the losses it causes: impairment of mental development, delayed growth and physical development, increased frequency of morbidities, among others. In this context, this article shows data collection from the last 10 years with the aim of clarifying the current prevalence of anemia in preschool children in Brazil and what are its main risk factors. To prepare this work, a systematic search was carried out in the electronic databases Virtual Health Library (VHL), PubMed/Medline, LILACS and SciELO. The results obtained show that iron deficiency anemia in preschool children is strongly associated with several sociodemographic, dietary and health factors.
Keywords: Preschool children; Risk factors; Prevention; Public health